2014
DOI: 10.1177/0004563214564400
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vitamin D replacement in patients with normocalcaemic and hypercalcaemic primary hyperparathyroidism and coexisting vitamin D deficiency

Abstract: Background: Vitamin D deficiency is increasingly recognized in patients with primary hyperparathyroidism but some clinicians are reluctant to replace vitamin D due to concerns with aggravating hypercalcaemia. We investigated the impact of vitamin D repletion in asymptomatic patients with normocalcaemic and hypercalcaemic primary hyperparathyroidism. Methods: This is a retrospective analysis of 111 patients with elevated parathyroid hormone concentrations (>6.4 pmol/L) referred to our endocrine clinic between J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
(53 reference statements)
1
8
0
Order By: Relevance
“…3 However, studies suggest that vitamin D supplementation reduces PTH without adversely affecting serum calcium. 6 Other cases have reported on a small proportion of patients who experience slightly elevated calcium levels after vitamin D treatment. Due to patient variability, long-term clinical follow-up and longer duration of treatment are necessary.…”
Section: Discussionmentioning
confidence: 97%
“…3 However, studies suggest that vitamin D supplementation reduces PTH without adversely affecting serum calcium. 6 Other cases have reported on a small proportion of patients who experience slightly elevated calcium levels after vitamin D treatment. Due to patient variability, long-term clinical follow-up and longer duration of treatment are necessary.…”
Section: Discussionmentioning
confidence: 97%
“…The presence of low serum 25OHD in subjects with PHP is wellestablished. (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) However, concurrently elevated serum 1,25 (OH)D concentrations in subjects with PHP have rarely been reported in the past 30 years. (15)(16)(17) This study also found normalization of mean concentrations of serum calcium, 25OHD, and 1,25(OH)D following a decline in circulating serum PTH levels after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This study also found a further rise in serum calcium on normalization of serum 25OHD consistent with most previous reports. (1,2,6,(15)(16)(17)20,21) In contrast, an isolated study has documented a lack of exaggerated rise in already existent hypercalcemia upon vitamin D supplementation. (12) However, in this study, 25OHD remained subnormal probably because of inadequate supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,16,18 In a 2015 study that included 23 patients with PHPT, vitamin D deficiency and normal calcium, 6 months' treatment with 1600-3200 IU per day did not provoke hypercalcaemia. 19 What is the clinical context for the patient with normocalcaemic hyperparathyroidism?…”
mentioning
confidence: 99%